Life and death on the Nile : a bioethnography of three ancient Nubian communities - Armelagos, George J. (University Press of Florida, 2018)
This work provides an account of half a century of scientific investigation of life and death in three ancient Nubian communities. The research coheres around a single, unifying theme: namely that the evolution and adaptation of human populations, both living and dead, results from a complex interaction between human biology and the cultural and natural environment. This has come to be known as a biocultural approach